A METHOD FOR CREATING PRACTICE-ORIENTED EDUCATIONAL PROGRAMS - Logachev, Maxim; Kuvarzina, Olga; Savvateev , Evgeniy; Kruglova, Elena; Sattorov , Shakhboz (Revista Inclusiones, 2020)
The article states the problem of training specialists in educational organizations. Modern specialist training in the Russian education system is oriented on the formation of knowledge and skills in a given subject area that increasingly falls behind the modern labor market requirements. The authors indicate the stages and methods of organizing the educational process in a way that would make professional competencies oriented towards the independence and responsibility of a specialist and their ability to identify their professional and educational needs in the context of innovative economic transformations independently the main element in the construction of educational programs.